UJI AKTIVITAS ANTIOKSIDAN PADA EKSTRAK KULIT JERUK MANIS (Citrus x sinensis) DENGAN METODE SPF SECARA SPEKTROFOTOMETRI UV-Vis - iswandi (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2021)
ABSTRACT Sweet orange peel (Citrus x sinensis) has benefits as an antioxidant and Sun Protecting Factor (SPF). This study aims to determine the antioxidant activity of sweet orange peel extract with 70% and 90% ethanol solvent variations using the Sun Protecting Factor (SPF) method. Sweet orange peel (Citrus x sinensis) was extracted using maceration method with 70% ethanol and 90% ethanol as solvent variations. The extract was then concentrated using a water bath. The extracts obtained were tested for phytochemicals for alkaloids, flavonoids, tannins, saponins and triterpenoids. The antioxidant activity test was carried out by dissolving each extract in absolute alcohol with a concentration of 20% (w/v). Antioxidant activity test using Sun Protecting Factor (SPF) method using UV-Vis spectrophotometer. The data was processed using One-Way Anova test statistics. The phytochemical test results on sweet orange peel extract showed that the extract contained positive alkaloids, flavonoids, saponins, tannins and triterpenoids. The antioxidant activity test on sweet orange peel extract showed that 70% alcohol solvent had a higher SPF value of 20,95, while the extract with 90% alcohol solvent had a lower SPF value of 15,70. Keywords: Citrus x sinensis, extract, maceration, UV-Vis spectrophotometer, SPF.